2023
DOI: 10.1021/jacs.2c13830
|View full text |Cite
|
Sign up to set email alerts
|

Parahydrogen-Polarized Fumarate for Preclinical in Vivo Metabolic Magnetic Resonance Imaging

Abstract: We present a versatile method for the preparation of hyperpolarized [1-13 C]fumarate as a contrast agent for preclinical in vivo MRI, using parahydrogen-induced polarization (PHIP). To benchmark this process, we compared a prototype PHIP polarizer to a state-of-the-art dissolution dynamic nuclear polarization (d-DNP) system. We found comparable polarization, volume, and concentration levels of the prepared solutions, while the preparation effort is significantly lower for the PHIP process, which can provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This is not necessary if higher hydrogen gas pressure and starting material concentration are used, to form fumarate in ≳200 mM concentration to allow direct precipitation from the reaction solution . 40 In high resolution 1 H NMR spectra we observed that the succinate formed was partially deuterated during the heterogeneous hydrogenation reaction (i.e., while the sample was in the presence of the heterogeneous catalyst). We carried out six additional 30 s hydrogenation experiments at 90 • C using 10, 15, and 20 wt.% Pd/Al2O3, and observed 16.5±1.5% deuteration of the succinate: 43% succinate-h4, 50% succinate-d1 and 8% succinate-2,3-d2.…”
Section: Forming Hyperpolarized Succinatementioning
confidence: 92%
“…This is not necessary if higher hydrogen gas pressure and starting material concentration are used, to form fumarate in ≳200 mM concentration to allow direct precipitation from the reaction solution . 40 In high resolution 1 H NMR spectra we observed that the succinate formed was partially deuterated during the heterogeneous hydrogenation reaction (i.e., while the sample was in the presence of the heterogeneous catalyst). We carried out six additional 30 s hydrogenation experiments at 90 • C using 10, 15, and 20 wt.% Pd/Al2O3, and observed 16.5±1.5% deuteration of the succinate: 43% succinate-h4, 50% succinate-d1 and 8% succinate-2,3-d2.…”
Section: Forming Hyperpolarized Succinatementioning
confidence: 92%
“…Hydrogenative PHIP generally uses homogeneous rhodium‐based catalysts for the addition of para‐H 2 to unsaturated precursors. This process requires specific chemistry (unsaturated precursor and optimal J coupling network in the product) and therefore, only a limited number of in vivo studies have been performed with HP‐ 13 C‐labeled metabolic probes generated by this technique [6–8] . Elegant work by Reineri and co‐workers overcame this limitation by parahydrogenating an unsaturated functional group attached to the substrate through a cleavable bond, typically an ester (side‐arm hydrogenation, SAH) [9–14] .…”
Section: Methodsmentioning
confidence: 99%
“…This process requires specific chemistry (unsaturated precursor and optimal J coupling network in the product) and therefore, only a limited number of in vivo studies have been performed with HP-13 C-labeled metabolic probes generated by this technique. [6][7][8] Elegant work by Reineri and co-workers overcame this limitation by parahydrogenating an unsaturated functional group attached to the substrate through a cleavable bond, typically an ester (side-arm hydrogenation, SAH). [9][10][11][12][13][14] SAH-PHIP often suffers from low 13 C polarization levels because of the weak long range J coupling between the heteroatom and the 1 H spins originating from para-H 2 .…”
mentioning
confidence: 99%
“…Parahydrogen-induced polarization (PHIP) techniques have emerged as promising candidates to address this need for efficient polarization methods. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] PHIP utilizes the nuclear spin singlet isomer of molecular hydrogen, parahydrogen (pH2), which acts as a cost-efficient source of hyperpolarization.…”
Section: F]fluorodeoxyglucose (Fdg) Positronmentioning
confidence: 99%